Language and Speech Problems Related to Carbamazepine in Benign Rolandic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
Language and speech problems in benign rolandic epilepsy (BRE) and changes occurring after treatment with carbamazepine (CBZ) monotherapy were investigated in 11 patients, ages 5 to 12 years, treated at Chonbuk National University, Medical School, Jeonbuk, Republic of Korea.